Gravitational scattering, inspiral, and radiation - AAVV, AAVV (Il Colle di Galileo, 2022)
The workshop gathered theorists working on different though connected areas concerning the recent discovery of gravitational waves. It fostered new collaborations between the quantum gravitational scattering amplitude and the general relativity community, leading to the calculation of new, high-order, terms in the post-Newtonian and post-Minkowskian perturbative approaches to the physics of binary systems, at both analytical and numerical level, in order to construct the waveform templates necessary for the analysis of LIGO/Virgo data. The use of recent progress on gravitational scattering and radiation in ultra-relativistic collisions of elementary particles or strings improved the determination of parameters appearing in the effective-one-body approach to the relativistic two-body problem. Various consequences of modified gravity theories for the LIGO/Virgo discoveries were also explored.